Dissection of Herzberg’s Two-Factor Theory to Predict Job Satisfaction: Empirical Evidence from the Telecommunication Industry of Pakistan - Seeham Yousaf (The Lahore Journal of Business)
Herzberg’s motivation theory is one of the most widely studied motivation theories. This theory is also known as the two-factor or dual-factor theory. The premise of Frederick Herzberg’s theory is that the concept of motivation is divided into two aspects: hygiene and motivators. There is no denying of the fact that the theory of Herzberg of employee motivation is very pertinent in explaining the work behaviors of organizational employees. Nevertheless, this theory attracts substantial criticism from its critics who strongly contended that there is no need to revive the original theory as it lacks substantial influence in explaining employee motivation. Taking this notion forward, this study aims to test the fundamental factors that are of six hygiene factors (extrinsic factors), and five motivators (intrinsic factors) that affect the job satisfaction of front line employees (FLEs). In doing so, this study moves beyond the dichotomy of these two factors and examine the pertinence of underlying factors that can directly influence the employee job satisfaction. The FLEs are the faces that represent organizations, as they directly interact with the customers at their business units. The study analyzes the data by applying a structured equation model on a survey sample of 284 employees, constituting of business managers and executives in both metropolitan and non-metropolitan areas in telecommunication industry of Pakistan. This research reveals positive and direct relationship of five of the underlying factors (money, relationship with peers, relationship with supervisors, work itself and recognition) with job satisfaction.